2019
DOI: 10.1007/s12011-019-01988-w
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure Assessment of Major and Trace Elements in Human Scalp Hair Among a Group of Eritrean Workers

Abstract: The aim of the study was to evaluate occupational exposure to 40 elements among a group of Eritrean adults employed at the Medeber metal market by analysing human scalp hair samples and by investigating the role of some predictors (gender, age, and body mass index-BMI) on their levels. Scalp hair samples were collected from 60 subjects (32 subjects working at the Medeber metal market and 28 subjects not working at Medeber and not employed in other industrial or artisanal activities) and were analysed through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Communities near mining may have unexpected dietary sources or can be exposed to other Hg species [12,53]. Since the Hg in hair is typically dominated by MeHg species [32], diet is often presumed to be the dominant exposure route; however, a fraction of Hg in hair could be the inorganic form caused by other dietary and non-dietary routes (e.g., inorganic Hg exposure from gold amalgamation) [12,54]. Laffont et al [54] found that modeled inorganic Hg levels in hair samples correspond well to measured inorganic Hg concentrations, demonstrating that inorganic Hg exposure sources to gold miners can be monitored by the use of hair samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communities near mining may have unexpected dietary sources or can be exposed to other Hg species [12,53]. Since the Hg in hair is typically dominated by MeHg species [32], diet is often presumed to be the dominant exposure route; however, a fraction of Hg in hair could be the inorganic form caused by other dietary and non-dietary routes (e.g., inorganic Hg exposure from gold amalgamation) [12,54]. Laffont et al [54] found that modeled inorganic Hg levels in hair samples correspond well to measured inorganic Hg concentrations, demonstrating that inorganic Hg exposure sources to gold miners can be monitored by the use of hair samples.…”
Section: Discussionmentioning
confidence: 99%
“…The hair-to-whole blood ratio has been estimated to be about 250 to 1 [30,31]. In this way, hair samples appear as an interesting alternative because it is a noninvasive matrix and it is easy to sample [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20 mg of each hair sample was washed according to a procedure described by Protano et al [9]. The washed samples were transferred into a polypropylene tube, mixed with 0.5 mL of 67% HNO 3 and 0.25 mL of 30% H 2 O 2 , and then were heated in the water bath for 20 min at 95 °C.…”
Section: Sample Pre-treatment and Analysismentioning
confidence: 99%
“…The analyte content in this matrix re ects the condition of the body and provides information on historical exposure from water, food by dermal exposure. HMA is considered to be a good screening tool in assessing the status of the human body with regard to essential and toxic elements, because the hair incorporates elements into its structure during growth [20]. Unlike other tissues, hair grows outside the skin and eliminates toxic elements from metabolic processes [21].…”
Section: Teethmentioning
confidence: 99%